2022
DOI: 10.3389/fnhum.2022.1057290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music intervention on subjective scores, heart rate variability, and prefrontal hemodynamics in patients with chronic pain

Abstract: IntroductionMusic interventions have been proposed in recent years as a treatment for chronic pain. However, the mechanisms by which music relieves pain are unclear, and the effects of music intervention on physiological indicators in patients with chronic pain remain to be explored. This study aimed to explore whether a music intervention would have effects on subjective pain ratings, heart rate variability, and functional connectivity of the cerebral cortex in patients with chronic pain.MethodsA randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…MI can affect multiple brain regions and facilitates the creation of new neural connections through various sensory modalities. For instance, previous studies have shown significant increases in functional connectivity between specific brain regions after patients received MI, including the bilateral dorsolateral prefrontal cortex and frontal areas [61], the dorsal anterior insula and posterior insular networks [62], and the right middle temporal gyrus [63]. Furthermore, functional magnetic resonance imaging (fMRI) [64] and nearinfrared spectroscopy (NIRS) [65] studies have also demonstrated increased activity in specific brain regions after receiving MI.…”
Section: Discussionmentioning
confidence: 99%
“…MI can affect multiple brain regions and facilitates the creation of new neural connections through various sensory modalities. For instance, previous studies have shown significant increases in functional connectivity between specific brain regions after patients received MI, including the bilateral dorsolateral prefrontal cortex and frontal areas [61], the dorsal anterior insula and posterior insular networks [62], and the right middle temporal gyrus [63]. Furthermore, functional magnetic resonance imaging (fMRI) [64] and nearinfrared spectroscopy (NIRS) [65] studies have also demonstrated increased activity in specific brain regions after receiving MI.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced plasma levels of adrenaline and nor-adrenaline have also been reported (Okada et al, 2009). While not directly linked to peripheral nociceptive processing, these indications of reduced sympathetic activity and stress are linked to changes in activity in frontal and prefrontal cortex and are important when considering the impact that anxiety can have, increasing the perception of chronic pain (Du et al, 2022).…”
Section: Autonomic Nervous Systemmentioning
confidence: 97%